THE EFFECT OF DIFFERENCES IN THE LENGTH OF SOAKING TIME FOR THE THYROXIN HORMONE ON THE GROWTH RATE OF FRESH WATER LOBSTER (Cherax quadricarinatus) - Muhammad Furqan Ramadhana; Agus Putra AS; Andika Putriningtias (JURNAL AKUAKULTURA, 2025)
Freshwater lobster is one of the lobster commodities that is not widely known by society today. Freshwater lobsters have a high selling value on the market, so information on growth hormones is needed to increase the growth of freshwater lobsters, so that they can meet market demand. Thyroxine hormone is a hormone produced by the thyroid gland which functions to form, store and release substances related to regulating metabolic rate. Therefore, this study aims to see how different soaking times for the thyroxine hormone affect the growth rate of freshwater lobsters and to determine the optimal time for soaking freshwater lobsters using the thyroxine hormone. The research method used in the research was a Completely Randomized Design (CRD) method with 4 treatments and 3 three replications. The treatments carried out were: PHT0 (control), PHT1 (soaking for 12 hours/0.1 mg/L), PHT2 (soaking for 24 hours/0.1 mg/L), PHT3 (soaking for 36 hours/0.1 mg/L). Parameters observed: Absolute Weight Growth, Absolute Length Growth, Daily Growth Rate, Survival Rate (SR), and Water Quality Observations. The results of the research showed that the best soaking time for the thyroxine hormone on the growth of freshwater lobsters (Cherax quadricarinatus) was in PHT2 (24 hours), and the lowest was in PHT0 (control) treatment.